Effects of Proprioception Exercises in the Rehabilitation Process of Football Players after Arthroscopic Surgery Anterior Cruciate Ligament (ACL) - Manouchehr Haidary (Islamic Azad University, Hamedan Branch, 2017)
Objective: The aim of this study was to test the effect of proprioception exercises in the rehabilitation process of football players after arthroscopic surgery on anterior cruciate ligament (ACL). Method: Data was collected from Specialist Hospital and Research Center in Rehabilitation, Medicine and Sports, Moscow, Russia. 20 patients with an average age of 16-25 years old with no historical records of neuromuscular diseases and injuries of the lower extremities. These were randomly divided into two groups: one experimental and one control. The experimental group were under monitoring for about five months, while they were doing proprioceptive exercises. Before and after the training period, the static equilibrium from the stork test and the dynamic performance of the star test were estimated and compared. Data were analyzed using Mann-Whitney and t-test with the significance threshold of (p<0.05). Results: through the proprioceptive exercise protocol, static and dynamic balance was significantly improved (p<0.001). Conclusion: This study confirmed that proprioception exercises classified from simple to complex according to sport fields in different phases of rehabilitation can positively affect the balance, the performance and quick return of football players to sports fields.